A STUDY OF ASSOCIATED PARTICLES AND 2ND-ORDER PROCESSES IN ELECTRON-PAIR PRODUCTION AT THE CERN INTERSECTING STORAGE-RINGS - Angelis, A; Basini, G; Besch, H; Breedon, R; Camilleri, L; Chapin, T; Cool, R; Cox, P; Vongagern, C; Grossopilcher, C; Hanna, D; Humphries, B; et al. (1984)
The multiplicity of particles associated with electron pairs with mass greater than 11 GeV/c2 is found to increase with the transverse momentum pT of the electron pair. The associated particles are observed to recoil against the electron pair and compensate locally its transverse momentum. The data are compared with lower √s dimuon data using the scaling form: s2pT2(d3 σ/dy dpT2 dm2) = H (xT, y, τ). © 1984.